Buried PM inner rotor magnetic gear evaluation. Issue 1 (September 2020) - Halim, M F M A; Sulaiman, Erwan; Jenal, Mahyuzie; R Othman, R N F K
Abstract: Inner rotor SFPMR glued on the rotor surface with material of high compressive strength but low tensile strength cannot sustain the centrifugal force in the high-speed operation, thus require retaining sleeve. Electrical motor employ the retaining sleeve to increase the rotor strength, but so far in MG, there are limited design that employ this technique. Another method to avoid PM from displaced is by buried into the rotor yoke. However, this method may result in lower torque and noise. In this paper, new MG structure is designed. The inner rotor surface mount PM of magnetic gear is rearrange as buried PM. First, the torque analysis of the MG is simulated without counting any loses. Then, gear efficiency is simulated over high speed range and compared to the original topology to identify the amount of reduction of the torque. The result agrees that the buried rotor reduced the torque output 3 times lower than the surface mount PM and disturb the torque which result in high torque ripple over 240%.